(R)-(−)-N-Isovalerylcamphorsultam - Wei Zhou; Shijie Zhang; Weixiao Hu (Acta Crystallographica Section E, 2009)
The title compound, C15H25NO3S, was prepared from (R)-(−)camphorsultam and isovaleryl chloride. The asymetric unit contains two independent molecules with slightly different conformations. In the crystal, weak intermolecular C—H...O hydrogen bonds link molecules into two independent hydrogen-bonded chains propagating along the a and b axes.